Knowledge levels and cervical cancer prevention behavior in women of reproductive age - Pipih Salanti (Poltekkes Kemenkes Bandung, 2026)
Background: Cervical cancer remains an important health problem among women in Indonesia, with high incidence and mortality rates. Low rates of early detection, limited HPV vaccination coverage, and insufficient knowledge among women of reproductive age about risk factors and prevention contribute to poor preventive behavior. Objective: This study aims to determine the relationship between the level of knowledge and cervical cancer prevention behavior among women of reproductive age at a midwife practice in Bogor. Methods: This study used a quantitative method with a cross-sectional design. A total of 261 respondents were selected using non-probability sampling, consisting of married women of reproductive age who received health services at an independent midwife practice in Bogor. Data were collected through a validated and reliable online questionnaire measuring knowledge level using a Guttman scale and prevention behavior using a Likert scale. Data analysis was performed using Spearman’s rho test to determine the strength of the relationship. Results: Most respondents had a low level of knowledge (70.9%) and low preventive behavior (79.3%). Statistical analysis showed a correlation coefficient of (moderate strength) and, indicating a significant relationship between knowledge level and cervical cancer prevention behavior among women of reproductive age at an independent midwife practice in Bogor. Conclusion: There is a significant relationship between knowledge levels and cervical cancer prevention behavior. Continuous health education by health workers through direct counseling, digital media, and empowerment of cadres is needed to increase knowledge and foster positive prevention behavior